Reactive power compensation for loss minimization in TNB distribution system / Mohamad Khairulnizam Abu Hassan - Abu Hassan, Mohamad Khairulnizam (2004)
This report presents the application of Artificial Immune System in determining compensating capacitor sizing for loss minimization in the power system. The proposed technique was tested on TNB distribution system and the Artificial Immune System program was developing using Borland C++ programming language. The developed Artificial Immune System is used to determine the size of the compensating capacitor located at the most end load bus with an objective to minimize the distribution losses. From the result it shows that the proposed technique is able to determine the suitable size of the compensating capacitor while satisfying the voltage constrain in order to minimize the losses in the system [1]